2015
DOI: 10.5334/jeps.cn
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Caregiving on the Development of Major Depressive Disorder and Generalized Anxiety Disorder

Abstract: Providing care for a relative is associated with psychological distress and a higher prevalence of psychological disorders. This study investigated the prevalence of anxiety and depressive disorders among the caregiving population. The study was based on data drawn from the Collaborative Psychiatric Epidemiology Surveys (CPES). Binary logistic regressions were conducted to examine these associations and to identify factors influencing the development of depressive and anxiety disorders. The analysis indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The sociodemographic characteristic of the caregiver of stroke survivors in our study (gender, age, employment status, educational level, relationship with the stroke survivor, and depression) was not significantly associated with depression. This finding is in agreement with previous studies that reported gender (27), age (24), employment status (28), and educational level of caregivers of post stroke survivors (29) was not associated with depression amongst caregivers of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…The sociodemographic characteristic of the caregiver of stroke survivors in our study (gender, age, employment status, educational level, relationship with the stroke survivor, and depression) was not significantly associated with depression. This finding is in agreement with previous studies that reported gender (27), age (24), employment status (28), and educational level of caregivers of post stroke survivors (29) was not associated with depression amongst caregivers of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…Mental health related conditions, anxiety, depression, and sleep difficulties were categorized according as those experiencing the condition with or without a diagnosis. In addition, the depression screening Patient Health Questionnaire (PHQ-9) score was used to characterize respondents depressive symptoms as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Sociodemographic and Health Characteristicsmentioning
confidence: 99%
“…In general, caregivers, regardless of their time investment, experience higher physical and psychological complications than non-caregivers [21]. Among caregivers, the humanistic and economic burden varies and is dependent on factors including the patient's disease [21][22][23][24] and its severity [25]. For example, caregivers of patients with psychiatric disorders experience higher rates of anxiety and depression compared to caregivers of patients with physical illness [21,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The potential negative outcomes of caregiving are extensive. Stress, 5,6 anxiety, 6,7 and depression 5,8 are common, as well as a decrease in overall health status 9 and cognitive abilities. 6,10 Caregivers may also experience role entrapment, 11 decreased self-esteem, 5 feelings of loneliness and isolation, 8,12 and unmet needs.…”
Section: Introductionmentioning
confidence: 99%